2015
DOI: 10.1155/2015/397924
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Cyclodextrinase fromThermococcus kodakarensisKOD1: Expression, Purification, and Enzymatic Characterization

Abstract: A gene encoding a cyclodextrinase from Thermococcus kodakarensis KOD1 (CDase-Tk) was identified and characterized. The gene encodes a protein of 656 amino acid residues with a molecular mass of 76.4 kDa harboring four conserved regions found in all members of the α-amylase family. A recombinant form of the enzyme was purified by ion-exchange chromatography, and its catalytic properties were examined. The enzyme was active in a broad range of pH conditions (pHs 4.0–10.0), with an optimal pH of 7.5 and a tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…[3] According to this study, the optimum temperature and pH for CDase are 65 C and 7.0, respectively. They are similar to those for CDase-Tk obtained from T. kodakarensis KOD1, [14] while they are different from CDase-Tc (from Thermococcus species CL1) [11] and CDase-Tp (Thermofilum pendens Hrk 5) [52] in which their optimum temperature and pH are 85 and 95 C and 5.0 and 5.5, respectively. CDase-ZNU had also high activity (>60%) at pHs ranging from 6.5 to 8.0 (compared to 100% at pH 7.0) showing that the enzyme can hydrolyze its substrates approximately in neutral pH.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…[3] According to this study, the optimum temperature and pH for CDase are 65 C and 7.0, respectively. They are similar to those for CDase-Tk obtained from T. kodakarensis KOD1, [14] while they are different from CDase-Tc (from Thermococcus species CL1) [11] and CDase-Tp (Thermofilum pendens Hrk 5) [52] in which their optimum temperature and pH are 85 and 95 C and 5.0 and 5.5, respectively. CDase-ZNU had also high activity (>60%) at pHs ranging from 6.5 to 8.0 (compared to 100% at pH 7.0) showing that the enzyme can hydrolyze its substrates approximately in neutral pH.…”
Section: Discussionsupporting
confidence: 73%
“…[48] According to other studies, the MW for CDase has been reported to be in the range of 62-90 kDa. [12][13][14]19] As a result of overexpression of recombinant enzymes and accumulation of high concentration of folding intermediates, molecular aggregates were formed in bacterial cell which could not be recovered. [49] Therefore, soluble proteins were purified for further studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The extracellular hydrolysis of starch is realized by secreting various enzymes that degrade the available starch polymers synergistically, such as amylases, pullulanase, amylopullulanase and cyclomaltodextrin glucanotransferase [59,[72][73][74][75][76]. Once imported in the cell, these maltooligosaccharides are further hydrolyzed intracellularly to either glucose or, via glucose-1-phosphate, to glucose-6-phosphate were they enter a modified Embden-Meyerhof (EM) pathway (Figure 1.3, box A-C) [59,76,77].…”
Section: Energy Metabolism and H 2 Productionmentioning
confidence: 99%